2023
DOI: 10.3389/fpls.2023.1107583
|View full text |Cite
|
Sign up to set email alerts
|

The responses of poplars to fungal pathogens: A review of the defensive pathway

Abstract: Long-lived tree species need to cope with changing environments and pathogens during their lifetime. Fungal diseases cause damage to trees growth and forest nurseries. As model system for woody plants, poplars are also hosts of a large variety of fungus. The defense strategies to fungus are generally associated with the type of fungus, therefore, the defense strategies of poplar against necrotrophic and biotrophic fungus are different. Poplars initiate constitutive defenses and induced defenses based on recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 119 publications
1
5
0
Order By: Relevance
“…How then do trees maintain their vigor in the face of persistent and evolving pathogen attacks over time? Recent studies have shown that poplars compared with Arabidopsis have evolved some unique defense mechanisms due to their longevity (Ullah et al, 2022; Zeng et al, 2023), but have so far received little attention in unique immune mechanisms of these perennials. In Arabidopsis , NPR1 is the master regulator of SA signalling for PR gene induction (Yu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…How then do trees maintain their vigor in the face of persistent and evolving pathogen attacks over time? Recent studies have shown that poplars compared with Arabidopsis have evolved some unique defense mechanisms due to their longevity (Ullah et al, 2022; Zeng et al, 2023), but have so far received little attention in unique immune mechanisms of these perennials. In Arabidopsis , NPR1 is the master regulator of SA signalling for PR gene induction (Yu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, like any other plants, including those of cultural importance, poplars are susceptible to various diseases caused by fungal, bacterial and viral pathogens that serve as natural regulators of ecological systems [24,25]. However, this fact imposes limitations on the practical use of poplars, as damage to leaves, wood and other parts of the trees contributes to reduced growth rate and increased mortality.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome pathogens, plants have developed various defence mechanisms and many physio-biochemical strategies to protect themselves against their attack [ 12 ]. One of the defence mechanisms of plants, including trees, against disease is the accumulation of phenolic compounds such as lignin, which increases during plant-pathogen interactions [ 13 , 14 ]. Plants accumulate cell wall aposites at sites of invasion by biotrophic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…ROS may promote the biosynthesis and accumulation of salicylic acid (SA), which is involved in the induction of systemic acquired resistance (SAR) in plants. SA plays an essential role in the signalling activated by plant pathogen-associated molecular patterns (PAMPs) [ 14 , 18 , 19 ]. Stress-activated increases in the content of phytohormones such as jasmonic acid (JA), ethylene (ET), and SA involved in various signalling pathways are pathogen-induced responses [ 14 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation